2011
DOI: 10.1166/jnn.2011.3835
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Reaction Kinetics and Impact Strength of Cyanate Ester Reinforced with Multiwalled Carbon Nanotubes

Abstract: In this work, the effect of multiwalled carbon nanotubes on the properties of a unique, low viscosity bisphenol E cyanate ester (BECy) resin is characterized during various stages of nanocomposite preparation. The effect of surface functionalization, with nanotubes containing hydroxyl groups (OH CNTs) and carboxylic acid groups (COOH CNTs), on the rheological, cure, thermal, and impact properties of the nanocomposite properties are also examined. Based on rheology measurements prior to cure, the unfunctionaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Interestingly, a paper showed that an increase in reaction rate can lead to a decrease in glass transition temperature. 60 As pointed out in a series of papers, 61,63 to properly determine the effect of adding carbon nanotubes to dispersion-reaction systems requires confirmation that the reaction itself is not affected by nanotubes. Possible interference is certainly more critical for thermosetting resins, and more difficult to measure (and, in the case of functionalized tubes, can even depend on whether functionalization occurs at the tips or along the sidewalls!).…”
Section: Dynamics: Glass Transition and Diffusion Coefficientmentioning
confidence: 99%
“…Interestingly, a paper showed that an increase in reaction rate can lead to a decrease in glass transition temperature. 60 As pointed out in a series of papers, 61,63 to properly determine the effect of adding carbon nanotubes to dispersion-reaction systems requires confirmation that the reaction itself is not affected by nanotubes. Possible interference is certainly more critical for thermosetting resins, and more difficult to measure (and, in the case of functionalized tubes, can even depend on whether functionalization occurs at the tips or along the sidewalls!).…”
Section: Dynamics: Glass Transition and Diffusion Coefficientmentioning
confidence: 99%
“…These are chosen based on the stronger interfacial interaction with this resin as reported earlier. 20 CNTs are functionalized with OH/ COOH content of 5%. The Fourier Transform Infrared Spectroscopy (FTIR) spectra to conform the type of functionalization are provided by the supplier and for the multi-walled carbon nanotubes (CNTs), SEM and TEM images along with Raman spectrum are provided.…”
Section: Methodsmentioning
confidence: 99%
“…Out of the limited literature available dealing with cyanate ester nanocomposites, Wang et al 19 reported that cyanate ester resin infused with 2 wt% CNTs functionalized with epoxy groups improved the impact and flexural strength by nearly 40% and 50%, respectively. Badrinarayanan et al 20 reported the use of low viscosity cyanate ester resin and studied the effect of CNTs with OH and COOH functional groups. They found that the impact strength of the resin increased by 91% and 63% on incorporation of 1 wt% COOH and OH CNTs, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The catalytic function of ZIF‐61 in the curing process of bisphenol A cyanate ester is induced by the Lewis acidity of ZIF‐61 which has an unoccupied orbital on the Zn atom . Multiwalled carbon nanotubes containing hydroxyl groups have exhibited the most dramatic catalytic effect on the polymerization of bisphenol E cyanate ester (CE) resin . 2,5‐Dihydroxyphenyl‐9,10‐dihydro‐9‐oxa‐10‐phosphaphenanthrene‐10‐oxide (DPDP) decreased the curing peak of the DPDP/CE system by 21–76 °C compared with that of the CE resin .…”
Section: Introductionmentioning
confidence: 99%